Brain Metastasis from Invasive Thymoma Mimicking Intracerebral Hemorrhage: Case Report - HARYU, Shinya (Neurol Med Chir (Tokyo), 2014)
A 55-year-old man with an 8-year history of invasive thymoma presented with sudden onset of left hemiparesis. Computed tomography (CT) and magnetic resonance (MR) imaging showed a right frontal lobe intracerebral hemorrhage and the possibility of brain metastasis could not be rejected. The patient underwent removal of the hematoma. Histological examination showed brain metastasis from invasive thymoma. To the best of our knowledge, this is the first reported case of hemorrhagic brain metastasis from invasive thymoma (non-cancerous) mimicking intracerebral hemorrhage.